Pendampingan Pemahaman Langkah Pembelajaran Bagi Siswa Kelas XII Pada Mata Pelajaran Akidah Akhlak Di MA Al-Islam Joresan - Badiul Khasanah; Binti Nur Lailatu Fadilah; Bisyarifati Hidayah; Cindy Avita Sari; Dhiya’ Ulhaq Salsabila; Nurul Malikah (Social Science Academic, 2025)
This article discusses the critical role of effective guidance provided by educators in the success of Akidah Akhlak learning. Teachers act as facilitators who not only deliver theoretical material but also motivate and guide students in applying moral values in their daily lives. Observations of the learning process in the 12th grade of MA Al-Islam Joresan Ponorogo revealed the use of a gradual approach, class discussions, personal reflections, and active learning methods. These steps aim to deepen students’ understanding of Akidah Akhlak and help them implement these values in real-life situations effectively. However, the study also highlights persistent challenges, such as the negative influence of the social environment and the lack of self-motivation among students. Addressing these issues requires a personal approach that considers individual student needs and strengthens collaboration between teachers, parents, and the community. Such collaborative efforts are essential to creating a supportive environment and ensuring the long-term success of Akidah Akhlak learning, both in academic and character development aspects.